Umbilical Cord Tissue Collection and Regenerative Medicine in a North Eastern Italy Region. Report about a Case of Inadequate Health Legislation - Sergio Parco; Silvia Perin (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2017)
We describe an exemplary case of inadequate health legislation and defensive medicine, regarding umbilical cord tissue collection for personal "private" use.